Deontic modal use in American English - Haskell, Janae (Kansas State University, 2013)
Modality, a concept for which linguists have struggled to come to an agreed-upon, comprehensive definition, has been the subject of many linguistic studies over the last several decades. The contemporary English modal system has a long history of semantic and morphological development, or grammaticalization, which currently consists of auxiliary modals that function with lexical verbs to express levels of obligation, necessity, ability, permission, and degrees of certainty. For native speakers of English, determining the appropriate contexts and form of a specific modal verb is second nature. However, grasping the contextual complexity of the English modal system can be difficult for English language learners. Deontic modals such as must, have to, have (got) to and should are often presented to English language learners as relatively equal in meaning and contextual appropriateness, which makes gaining a native-like command of these modals even more difficult. This study, on a small scale, describes contemporary usage through a comparison of similar studies and data from a series of sociolinguistic interviews with native speakers of American English. The participants range from the ages of 25-50. They were chosen from the local population of Manhattan, KS and have lived in Kansas for a minimum of 10 years. Through a quantitative analysis of the tokens, patterns of dialogic use will be extrapolated from the linguistic data. The research questions will seek to find established patterns of deontic modal use that in order to identify practical applications of usage-based research for textbook publishers, curriculum designers, and educators.
Keywords: Deontic; Epistemic; Modality; Grammaticalization; English as a Second Language (0441); Language, Linguistics (0290)